Microsoft Office 365 on Learning History Subject - Jamiludin Jamiludin; Darnawati Darnawati; Sukadi Linta; Anugrah Puspita Ayu Muhammad; Waode Ade Sarasmita Uke (JETL (Journal of Education, Teaching and Learning), 2021)
This research aimed at knowing the students' perception of Microsoft Office 365 on learning history. This research used a quantitative descriptive design. It was conducted at SMAN 4 Kendari, Southeast Sulawesi. The sample of this study was students in XI-1 grade. The students were 46. Research instruments used questionnaires and interviews. The result showed that the students had a positive response toward the use of Microsoft Office 365. Besides, 87% of students agree that they can understand History Subject during online learning. The most frequently used features were Teams (95.7%), SharePoint (2.2%), and Forms (2.2%). THowever, the obstacle of using this application is if students do not have facilities such as a good internet network, and laptops.